How to Diagnose Endometriosis in Adolescents Early - Hartati, Hartati; Pratiksa, Dannah Khalizha Nabila (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Endometriosis is one of the reproductive disorders in women that has severe symptoms and affects activities. Globally, endometriosis is estimated to affect around 10% of women of reproductive age, or around 190 million women worldwide. However, the diagnosis of endometriosis is still very slow with an average delay of 4 to 12 years from the first symptoms. This study aims to provide information on how to detect endometriosis early in adolescents. When is the best time to do early detection, what are the factors for late diagnosis, and what are the disadvantages that can occur if the diagnosis is late. This writing method is a literature study with literature sources for the last 5 years through search sites such as google scholar, Pubmed, NCBI, Clinical Key, and Science Direct. The results obtained from these various literature sources are Early detection is very important since adolescence, especially if there is severe dysmenorrhea or chronic pelvic pain. Delay in diagnosis is caused by the normalization of dysmenorrhea, lack of accurate non-invasive diagnostic tools, and low public awareness. As a result, patients are at risk of experiencing impaired quality of life.